Effect of pretreatment with a P2Y12 inhibitor in patients with non-ST-elevation acute coronary syndrome: a systematic review and network meta-analysis - Li, Yachao; Lei, Mengjie; Zhao, Zhigang; Yang, Yanli; An, Lei; Wang, Jingyao; Sun, Xue; Li, Cairong; Xue, Zengming (Frontiers in Cardiovascular Medicine, 2023)
Background: This study aimed to systematically evaluate the effects of different types and doses of pretreatment with P2Y12 inhibitors in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) undergoing percutaneous coronary intervention (PCI). Methods: Electronic databases were searched for studies comparing pretreatment with different types and doses of P2Y12 inhibitors or comparison between P2Y12 inhibitor pretreatment and nonpretreatment. Electronic databases included the Cochrane Library, PubMed, EMBASE, and Web of Science. Literature was obtained from the establishment of each database until June 2022. The patients included in the study had pretreatment with P2Y12 inhibitors with long-term oral or loading doses, or conventional aspirin treatment (non-pretreatment). The primary endpoint was major adverse cardiac and cerebrovascular events (MACCEs) during follow-up within 30 days after PCI, which included determining the composite endpoints of cardiac death, myocardial infarction, ischemia-driven revascularization, and stroke. The safety endpoint was a major bleeding event. Results: A total of 119,014 patients from 21 studies were enrolled, including 13 RCTs and eight observational studies. A total of six types of interventions were included—nonpretreatment (placebo), clopidogrel pre-treatment, ticagrelor pretreatment, prasugrel pretreatment, double loading pretreatment (double loading dose of clopidogrel, ticagrelor, prasugrel) and P2Y12 inhibitors pretreatment (the included studies did not distinguish the types of P2Y12 inhibitors, including clopidogrel, ticagrelor, and prasugrel). The network meta-analysis results showed that compared to patients without pretreatment, patients receiving clopidogrel pretreatment (RR=0.78, 95% CI:0.66, 0.91, P<0.05) and double-loading pretreatment (RR=0.62, 95% CI:0.41, 0.95, P<0.05) had a lower incidence of MACCEs. There was no statistically significant difference in the incidence of major bleeding events among the six pretreatments (P > 0.05). Conclusions: In patients with NSTE-ACS, pretreatment with P2Y12 inhibitors before percutaneous intervention reduced the incidence of recurrent ischemic events without increasing the risk of major bleeding after PCI compared with nonpretreatment. Clopidogrel or double loading dose P2Y12 inhibitors can be considered for the selection of pretreatment drugs.